Penerapan SAK EMKM Dalam Penyusunan Laporan Keuangan Usaha Mikro, Kecil, Dan Menengah (International Forum of Researchers and Lecturers, 2023)
Currently, the MSME financial reporting standard uses SAK EMKM (Standard for Financial Accounting for Micro, Small and Medium Entities). MSME accounting is expected to make and create more structured financial reports. The purpose of this research is to find out how SAK EMKM is applied in preparing financial reports for MSMEs, and to find out what are the obstacles encountered in preparing SAK EMKM-based financial reports. The design used is literature review, articles are collected using search engines such as Google Scholar and Garuda. Based on the research results collected and the author's analysis, it was found that there are still many MSMEs in Indonesia that do not make or use accounting information to run their business. Therefore, when asked about the amount of their assets, they could not provide any information. Small business owners lack accounting knowledge and many of them do not understand the importance of accounting for business continuity and business success.